“I want to learn English after retirement”: The blended learning experiences of senior citizens - Dos Santos, Luis M.; Kwee, Ching Ting Tany (Frontiers in Education, 2022)
Life-long learning is one of the educational topics in countries and regions in the East Asia region. Currently, many senior citizens decide to gain their English language proficiencies and skills after their retirement in Hong Kong SAR. Although Chinese and English are the official languages in Hong Kong SAR, many senior citizens cannot handle both languages due to their previous education and background. The purpose of this study is to understand the learning motivations and experiences of a group of senior citizens in Hong Kong, particularly with regard to using the blended learning mode as the means for instruction during the COVID-19 pandemic. With the coordination of adult learning centre, 40 participants who were taking a blended English-as-an-Additional Language course were joined the study. The online-based semi-structured interview and focus group activities were employed. In line with the social cognitive career and motivation theory and self-efficacy theory, the results indicated that: 1) achieve my personal goals, 2) I want to speak English as my additional language, and 3) life-long learning as my development, were the main themes. The results of this study provided some suggestions to programme managers, course leaders, school heads, and human resources planners for the directions in life-long learning and foreign language or additional language learning to senior citizens in the metropolitan regions.